12 + 12 = 9

13 + 13 = ?

You have to develop a system that explains that first two answers and then apply that system to the third equation. So this question might not have just one right answer...

You can create a system that for example adds up the digits of the numbers and then multiplies like so:

11 + 11 = 4

(1+1) * (1+1) = 4

2 * 2 = 4

12 + 12 = 9

(1+2) * (1+2) = 9

3 * 3 = 9

13 + 13 = ?

(1+3) * (1+3) = ?

4 * 4 = ?

4 * 4 = 16

Answer: 13 + 13 = 16

- All categories
- Pre-Algebra Answers 12,330
- Algebra 1 Answers 25,321
- Algebra 2 Answers 10,467
- Geometry Answers 5,194
- Trigonometry Answers 2,642
- Calculus Answers 6,033
- Statistics Answers 3,029
- Word Problem Answers 10,149
- Other Math Topics 6,686

81,851 questions

86,190 answers

2,224 comments

69,792 users